Review paperSevere skin complications in patients treated with antidepressants: a literature review - Herstowska, Marta; Komorowska, Olivia; Cubała, Wiesław J.; Jakuszkowiak-Wojten, Katarzyna; Gałuszko-Węgielnik, Maria; Landowski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Clinical manifestations of drug-induced skin reactions include a wide range of symptoms, from mild drug-induced exanthemas to dangerous and life-threatening generalized systematic reactions. Adverse drug reactions of low risk include phenomena such as drug-induced rashes, phototoxic reactions, eczemas and urticarias, which appear most often when the medication is being introduced. Drug-induced skin reactions to psychotropic medication are usually associated with antiepileptic drugs. However, a significant role can be assigned to selective serotonin reuptake inhibitors. The aim of this paper is to review a spectrum of severe skin complications in patients treated with antidepressants with the indication of their clinical monitoring and management.